PENGARUH TATA KELOLA PERUSAHAAN, DISPERSI KEPEMILIKAN, BIAYA KEPEMILIKAN PADA KINERJA KEUANGAN PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tilka Hayaton; A. Sakir (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
This study aimed to analyze the effect of corporate governance, dispersion ownership, cost ownership on financial performance. Corporate governance measured by CGPI (Corporate Governance Perception Index) based on the rating that has been prepared by IICG (Indonesian Institute of Corporate Governance), dispersion ownership measured  by adding up the shares owned by the public and the number of shares outstanding. Cost ownership is measured by dividends per share and earnings per share. As well as the financial performance measured by the value of Return On Equity and Tobin’s Q .Sampling technique used is purposive sampling. Data analysis techniques for banking companies listed on the Indonesia Stock Exchange (BEI) in the period 2012-2017. It was found that corporate governance has a negative and significant effect on the bank financial performance (Return On Equity, Tobin’s q). Dispersion ownership has a negatif and significant effect on the bank financial performance. Cost ownership has  a negatif and significant effect on the bank financial performance.